Constructing nickel-based bifunctional oxygen catalyst and dual network hydrogel electrolyte for high-performance, compressible and rechargeable zinc-air batteries. (December 2022) - Hang, Lifeng; Zhang, Tao; Men, Dandan; Liang, Lianbao; Chen, Yiyu; Jiang, Guihua
Abstract: Wearable Zn-air battery (ZAB) delivers great potential for the next-generation wearable electronic devices. It requires the ZAB accommodating not only the high-power, high efficiency but also the mechanical stability even subjected to largely compression force. However, it remains a great challenge to obtain the highly efficient O2 catalyst as well as the compressible electrolyte. Herein, we constructed a high-performed and compressible ZAB based on the Ni-based bifunctional O2 catalyst and designed a dual network hydrogel electrolyte for outstanding electrochemical and mechanical performance. The as-obtained compressible ZAB based on the Ni-NC catalyst and the hydrogel electrolyte could exhibited an open-circuit voltage of 1.44 V, a peak power density of 87.7 mW cm −2, and an energy efficiency of ∼58%. When the ZAB being compressed up to 50%, the maximum power density could retain at 69.3%. This research could provide new insights for applying the Ni-NC catalyst and the dual network hydrogel to obtain high-performance wearable ZAB. Graphical abstract: Image 1 Highlights: Ni-nitrogen-carbon as outstanding bifunctional O2 activity with the potential gap (ΔE) as 0.83 V. Dual-network hydrogel electrolyte with high mechanical compression up to 92% deformation. High ionic conductivities as 27.5 mS cm −1 . Compressible ZAB with a stable open-circuit voltage of 1.44 V. A high power density of 87.7 mW cm −2 with the maximum power density retaining at 69.3%.